The design, fate and impact of a hospital-wide training program in evidence-based medicine for physicians – an observational study - Thor, Johan; Olsson, Daniel; Nordenström, Jörgen (BMC medical education, 2016)
Background Many doctors fail to practice Evidence-Based Medicine (EBM) effectively, in part due to insufficient training. We report on the design, fate and impact of a short learner-centered EBM train-the-trainer program aimed at all 2400 doctors at the Karolinska University Hospital in Sweden on the heels of a tumultuous merger, focusing particularly on whether it affected the doctors’ knowledge, attitudes and skills regarding EBM. Methods We used a validated EBM instrument in a before-and-after design to assess the impact of the training. Changes in responses were analyzed at the individual level using the Wilcoxon matched pairs test. We also reviewed documentation from the program – including the modular EBM training schedule and the template for participants’ Critically Appraised Topic reports – to describe the training’s content, design, conduct, and fate. Results The training, designed to be delivered in modules of 45 min totaling 1.5 days, failed to reach most doctors at the hospital, due to cost cutting pressures and competing demands. Among study participants ( n = 174), many reported suboptimal EBM knowledge and skills before the training. Respondents’ strategies for solving clinical problems changed after the training: the proportion of respondents reporting to use (or intend to use) secondary sources “Often/very often” changed from 5 % before the training to 76 % after the training; in parallel, reliance on textbooks and on colleagues fell (48 to 23 % and 79 to 65 %, respectively). Participants’ confidence in assessing scientific articles increased and their attitudes toward EBM became more positive. The proportion of correct answers in the EBM knowledge test increased from 52 to 71 %. All these changes were statistically significant at p < 0.05. Conclusions Many study participants, despite working at a university hospital, lacked basic EBM knowledge and skills and used the scientific literature suboptimally. The kind of short learner-centered EBM training evaluated here brought significant improvements among the minority of hospital doctors who were able to participate and, if applied widely, could contribute to better, safer and more cost-effective care.